Modified lay-open (incision, curettage, partial lateral wall excision and marsupialization) versus total excision with primary closure in the treatment of chronic sacrococcygeal pilonidal sinus - (:unkn) unknown (SPRINGER, 2005)
Background and aims: The best surgical technique for treating pilonidal sinus disease is controversial. The aim of this study is to compare the modified lay-open technique with primary closure following excision with respect to operating time, healing time, time before return to work, morbidity rate, and recurrence rate. Patients and methods: After a pre-study power analysis, 142 patients with chronic sacrococcygeal pilonidal sinus were prospectively and randomly allocated, either to the modified lay-open group (Group A, n=73) or the primary closure group (Group B, n=69). In the former, incision, curettage, partial lateral wall excision, and marsupialization were performed. Single doses of cefazoline (1 g) and metronidazole (500 mg) were given intravenously 15 min before surgery to all patients. Results: There were no differences with respect to gender, age, body mass index, and mean operating time between the groups. In Group A, healing failure and early bridging occurred in one patient each. In Group B, wound infection occurred in four patients, wound breakdown in three, one healing failure and hematoma in one patient each. Morbidity and recurrence rates were significantly lower in Group A (2.7 vs. 13%, P=0.028 and 1.4 vs. 17.4%, P < 0.001 respectively). The median time before return to work in Group A was significantly shorter than in Group B (3 [range 2-8] vs. 21 [range 14-63] days, P < 0.001). The median healing time in Group A was significantly longer than in Group B (7 [range 3-16] weeks vs. 2 [range 2-9] weeks; P < 0.001). Conclusion: The results of the present study suggest that modified lay-open is superior to excision with primary closure for the surgical treatment of chronic sacrococcygeal pilonidal sinus with regard to morbidity and recurrence rates, and time before return to work, although healing time is longer.
Keywords: pilonidal sinus; lay-open; total excision with primary closure; recurrence; RANDOMIZED TRIAL; KARYDAKIS FLAP; PRIMARY SUTURE; LIMBERG FLAP; DISEASE; EXPERIENCE; DRAIN